Potential Risk of Lumpy Skin Disease Virus on Animal Health and Its Products - Amir Gomaa,; Randa Mahmoud,; Abdulsalam Saleh,; Salah Eldein Abrayk,; Mohammd Abd Alati,; Jalalbu Hawiyah, (AlQalam Journal of Medical and Applied Sciences, 2023)
The purpose of this study is to quantify the risk of lumpy skin disease (LSDV) in Libya, with a focus on the cities of Al-Marj and Al-Jabal Al-Akhdar, as well as the effect this illness has on animal products such as gum and meat and its derivatives. Effective and proper risk management is necessary because LSDV poses a serious threat to animals and the dairy and meat products that they produce throughout all of Libya, particularly along the Green Mountain Coast. Neglecting epidemiology has disastrous effects. Following the proper health checks is essential to overcoming this, particularly in light of the unguarded borders and the smuggling of diseased animals. The illness spreads, making it very challenging to eradicate. Livestock travel over long distances and wind-borne disease vectors are two factors in the spread of LSD. As a result, the disease's appearance across the nation escalates into an epidemic. This study was conducted after a qualitative examination of the disease's hazards.